Discovery of biaryl carboxylamides as potent RORγ inverse agonists. Issue 15 (1st August 2015) - Chao, Jianhua; Enyedy, Istvan; Van Vloten, Kurt; Marcotte, Douglas; Guertin, Kevin; Hutchings, Richard; Powell, Noel; Jones, Howard; Bohnert, Tonika; Peng, Chi-Chi; Silvian, Laura; Hong, Victor Sukbong; et al.
Graphical abstract: Abstract: RORγt is a pivotal regulator of a pro-inflammatory gene expression program implicated in the pathology of several major human immune-mediated diseases. Evidence from mouse models demonstrates that genetic or pharmacological inhibition of RORγ activity can block the production of pathogenic cytokines, including IL-17, and convey therapeutic benefit. We have identified and developed a biaryl-carboxylamide series of RORγ inverse agonists via a structure based design approach. Co-crystal structures of compounds16 and48 supported the design approach and confirmed the key interactions with RORγ protein; the hydrogen bonding with His479 was key to the significant improvement in inverse agonist effect. The results have shown this is a class of potent and selective RORγ inverse agonists, with demonstrated oral bioavailability in rodents.